2010
DOI: 10.1260/1747-9541.5.3.373
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Approach on Spike Jump Height for Female Volleyball Players

Abstract: The purpose of the study was to compare vertical jump height using a four-step approach volleyball spike jump (VBSJ) and a standing counter-movement jump (CMJ) for competitive female volleyball players. Ten NCAA Division I female volleyball players were recruited. Each participant performed jumps using two techniques: a four-step approach VBSJ and a standing CMJ. Mean jump height for the VBSJ (0.38 ± 0.06 m) was significantly greater than the CMJ (0.33 ± 0.05 m). No correlation between jump height and horizont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…The different roles of both legs in stopping and transferring horizontal velocity are a major finding of this study as well as other studies that hypothesised different mechanics in spike jumps between sexes. Hsieh and Christiansen (2010) indicated that in females, the approach may be used to maximise muscle function rather than to increase horizontal velocity as it is common in males. As shown by the higher horizontal impulse on FP2 compared with FP1, the main responsibility for velocity transfer lies clearly in the non-dominant leg as reported by Wagner et al (2009).…”
Section: Discussionmentioning
confidence: 99%
“…The different roles of both legs in stopping and transferring horizontal velocity are a major finding of this study as well as other studies that hypothesised different mechanics in spike jumps between sexes. Hsieh and Christiansen (2010) indicated that in females, the approach may be used to maximise muscle function rather than to increase horizontal velocity as it is common in males. As shown by the higher horizontal impulse on FP2 compared with FP1, the main responsibility for velocity transfer lies clearly in the non-dominant leg as reported by Wagner et al (2009).…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, no previous research has examined the effect of the different relay start techniques on the underwater phase, while this is the fastest race segment (Cossor & Mason, 2001;Naemi & Sanders, 2008;Thow et al, 2012), especially for elite level swimmers (Veiga et al, 2014(Veiga et al, , 2016. Only when measuring vertical jump performance, the horizontal approach has been identified as an essential influence on jump height (Hsieh & Christiansen, 2010) which could suggest a superior potential of relay start step techniques.…”
Section: Introductionmentioning
confidence: 99%
“…This helped improve the ability of hip, thigh and leg muscles using muscle elasticity before contraction by shortening to give them motor speed through the highest strength and speed possible, which is one of the requirements of volleyball skill performance such as the spike skill. (Hsieh & Christiansen, 2010).…”
Section: Discussionmentioning
confidence: 99%